Elevated Expression of Chemokine CXCL13 in Chronic Hepatitis B Patients Links to Immune Control during Antiviral Therapy - Liu, Chao; Huang, Xuan; Werner, Melanie; Broering, Ruth; Ge, Jun; Li, Yongyin; Liao, Baolin; Sun, Jian; Peng, Jie; Lu, Mengji; Hou, Jinlin; Zhang, Xiaoyong (Frontiers in Immunology, 2017)
C-X-C-chemokine ligand 13 (CXCL13), the ligand for C-X-C chemokine receptor type 5 (CXCR5), is a major regulator of B-cell trafficking and plays an integral role in age-dependent clearance of hepatitis B virus (HBV) in the mouse model. However, the expression and function of CXCL13 in patients with chronic hepatitis B (CHB) remains unknown. By use of liver cell subpopulations isolated from CHB patients, we found that CXCL13 mRNA was abundantly expressed in Kuppfer cells (KC), but not in primary hepatocytes, liver sinusoidal endothelial cells and hepatic stellate cells. Interestingly, KC isolated from HBV positive liver had much higher level of CXCL13 expression than non-HBV infected controls. And its expression was induced by toll-like receptor 3 ligand poly I:C stimulation. Moreover, intense expression of CXCL13 protein and accumulation of CD4+ T and B cells were evident in follicular-like structures in the liver tissue of CHB patients, which indicated its chemotactic effect on CXCR5+CD4+ cells and B cells. Consistently, the levels of serum CXCL13 were significantly higher in the CHB patients than in healthy controls. Furthermore, CXCL13 concentration was increased in the complete response (CR) group during week 0 to 12 and did not change significantly during the course of telbivudine treatment, compared with the patients who didn't achieve CR. In conclusion, the HBV-related increase of CXCL13 production in KC and serum CXCL13 level during telbivudine treatment might be associated with immune control of chronic HBV infection.